2006
DOI: 10.1007/s00268-006-0354-4
|View full text |Cite
|
Sign up to set email alerts
|

Early Video‐Assisted Thoracic Surgery for Primary Spontaneous Hemopneumothorax

Abstract: Our study suggests that surgery should be undertaken for PSHP as soon as possible after the clinical condition has stabilized. Under this strategy, VATS is an acceptable approach. It allows a shorter hospital stay and is exempt from unnecessary blood transfusion. Later complications, such as empyema and impaired lung reexpansion, can also be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 32 publications
0
37
0
3
Order By: Relevance
“…Some studies have concluded that conservative treatment is adequate if bleeding persists less than 24 hours after chest tube insertion [8]. However, if the patients with PSHP are initially managed nonoperatively, most of them ultimately undergo surgery for one of the following conditions: refractory clinical deterioration (profuse blood loss), reappearance of an unstable condition (rebleeding), and later complications (reactive fluid collection, clot empyema, or persistent air leak) [4]. Recent studies have been concerned with the importance of early and aggressive treatment of PSHP in the stable condition [4,7].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Some studies have concluded that conservative treatment is adequate if bleeding persists less than 24 hours after chest tube insertion [8]. However, if the patients with PSHP are initially managed nonoperatively, most of them ultimately undergo surgery for one of the following conditions: refractory clinical deterioration (profuse blood loss), reappearance of an unstable condition (rebleeding), and later complications (reactive fluid collection, clot empyema, or persistent air leak) [4]. Recent studies have been concerned with the importance of early and aggressive treatment of PSHP in the stable condition [4,7].…”
Section: Discussionmentioning
confidence: 98%
“…Unlike other spontaneous hemothorax events caused by malignancy, congenital cystic adenomatoid malformation, or coagulopathy, the mechanisms of bleeding in PSHP are well described [6]. Primary spontaneous hemopneumothorax most commonly results from torn adhesions of the pleura, rupture of vascularized bullae, and torn congenital aberrant vessels between the parietal pleura and bulla [4,6]. Some authors have stated that the peculiarity of PSHP is a sustained hemorrhage resulting from negative intrapleural pressure and an abnormal structure of the ruptured vessel.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations